Cell-Penetrating and Targeted Peptides Delivery Systems as Potential Pharmaceutical Carriers for Enhanced Delivery across the Blood-Brain Barrier (BBB) - Soma Mondal Ghorai; Auroni Deep; Devanshi Magoo; Chetna Gupta; Nikesh Gupta (MDPI AG, 2023)
Among the challenges to the 21st-century health care industry, one that demands special mention is the transport of drugs/active pharmaceutical agents across the blood-brain barrier (BBB). The epithelial-like tight junctions within the brain capillary endothelium hinder the uptake of most pharmaceutical agents. With an aim to understand more deeply the intricacies of cell-penetrating and targeted peptides as a powerful tool for desirable biological activity, we provide a critical review of both CPP and homing/targeted peptides as intracellular drug delivery agents, especially across the blood-brain barrier (BBB). Two main peptides have been discussed to understand intracellular drug delivery; first is the cell-penetrating peptides (CPPs) for the targeted delivery of compounds of interest (primarily peptides and nucleic acids) and second is the family of homing peptides, which specifically targets cells/tissues based on their overexpression of tumour-specific markers and are thus at the heart of cancer research. These small, amphipathic molecules demonstrate specific physical and chemical modifications aimed at increased ease of cellular internalisation. Because only a limited number of drug molecules can bypass the blood-brain barrier by free diffusion, it is essential to explore all aspects of CPPs that can be exploited for crossing this barrier. Considering siRNAs that can be designed against any target RNA, marking such molecules with high therapeutic potential, we present a synopsis of the studies on synthetic siRNA-based therapeutics using CPPs and homing peptides drugs that can emerge as potential drug-delivery systems as an upcoming requirement in the world of pharma- and nutraceuticals.